Political decision-making and security intelligence recent techniques and technological developments - Dall'Acqua, Luisa 1962; Gironacci, Irene M. 1988 (Advances in electronic government, digital divide, and regional development (AEGDDRD) book series, 2020)
""This book examines the main techniques of intelligence analysis to prevent terrorism and political attacks conducted by state/non-state actors. It also explores the use of new technologies as investigative tools and training"--Provided by publisher"--